Comparison of Emergency Department Patients to Inpatients Receiving a Pulmonary Embolism Response Team (PERT) Activation. (11th May 2017) - Deadmon, Erin K.; Giordano, Nicholas J.; Rosenfield, Kenneth; Rosovsky, Rachel; Parry, Blair Alden; Al‐Bawardy, Rasha Fahad; Chang, Yuchiao; Kabrhel, Christopher
Abstract: Objectives: The development of pulmonary embolism response teams (PERTs) has been widely adopted nationally with the goal of providing multidisciplinary care to patients with high‐risk PE. Most PERT activations originate from the emergency department (ED), while others are from the intensive care unit (ICU) or inpatient floors. It is unclear if ED PERT activations differ from non‐ED PERT activation in terms of presentation, management, and outcome. Methods: We enrolled a consecutive cohort of patients for whom PERT was activated at an urban academic medical center. We compared three groups of PERT activations based on whether the activation originated from the ED, ICU, or a non‐ICU inpatient floor. We compared these groups in terms of the proportion of PERT activations that occurred during day, evening, or weekend hours and the proportion of confirmed PE. We also compared PE severity, treatment, and outcomes across locations. We tested differences using chi‐square tests, with a two‐tailed p‐value of <0.05 considered statistically significant. Results: We enrolled 561 patients, of whom 449 (79.5%) had confirmed PE. The mean ± SD age of patients with confirmed PE was 61 ± 17 years, and 300 (53.5%) were male. Activations from the ED ( n =  283, 88.4%) or floor ( n =  100, 74.6%) were more likely to be for confirmed PE than activations from the ICU ( n =  63, 58.9%; p < 0.0001). There was a statistical difference in the time of day of PERT activation with the ED having more activations during night hours than the ICU or floors (p = 0.004). Most activations for confirmed, massive PE originated from the ICU ( n =  41, 65.1%), followed by the ED ( n =  82, 29%) and inpatient floors ( n =  22, 22%; p < 0.0001). Most activations from the ED ( n =  155, 54.8%) and floors ( n =  55, 55%) were for submassive PE. The use of thrombolysis or thrombectomy was more common among ICU patients ( n =  18, 33.3%), followed by ED patients ( n =  53, 19.6%) and then floor patients ( n =  8, 8.2%). Mortality and major bleeding events were most common among ICU patients and similar among ED and floor patients. Conclusions: Pulmonary embolism response team activations from different clinical locations differ in terms of patient presentation, PE confirmation, treatments, and outcomes. PERTs should be customized to support the different needs of each clinical area.